APLIKASI METODE FUZZY CLUSTERING MEANS UNTUK DATA TRENDING KASUS VAKSIN CORONA PADA JEJARING SOSIAL TWITTER - Damaris Lalang; Mariam Lanmay (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2022)
Prevention of the spread of the 2019 corona virus disease by vaccination has become a controversy in a long conversation on Twitter social media. One way to classify these conversations is to use fuzzy clustering means. Fuzzy clustering means is used to group data into several classes with a high degree of similarity, therefore in the study entitled